ChemInform Abstract: Direct Amination of Phenols under Metal‐Free Conditions. Issue 44 (14th October 2013) - Yu, Jianzhong; Wang, Yongtao; Zhang, Peizhi; Wu, Jun
Abstract A convenient protocol employing α‐bromo‐propionamides as aminating reagents is developed for the direct amination of phenols.